2013
DOI: 10.1073/pnas.1213083110
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide photolysis from 150 to 210 nm: Singlet and triplet channel dynamics, UV-spectrum, and isotope effects

Abstract: We present a first principles study of the carbon dioxide (CO 2 ) photodissociation process in the 150-to 210-nm wavelength range, with emphasis on photolysis below the carbon monoxide + O( 1 D) singlet channel threshold at ∼167 nm. The calculations reproduce experimental absorption cross-sections at a resolution of ∼0.5 nm without scaling the intensity. The observed structure in the 150-to 210-nm range is caused by excitation of bending motion supported by the deep wells at bent geometries in the 2 1 A′ and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
109
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 45 publications
7
109
0
Order By: Relevance
“…For photolysis of N 2 O, results from ab initio calculations agree better with experimentally determined isotope fractionations than semiempirical calculations [ Schmidt et al , ]. For CO 2 , the ab initio calculations [ Schmidt et al , ] reported 3 times stronger fractionations than predicted by the semiempirical approach applied by Liang et al []. Furthermore, Ndengué et al [] showed that the assumption by Liang et al [] of a proportional relationship between changes in absorption cross sections under isotopic substitution and changes in zero point energy for both central and terminal substitution is not valid.…”
Section: Discussionmentioning
confidence: 99%
“…For photolysis of N 2 O, results from ab initio calculations agree better with experimentally determined isotope fractionations than semiempirical calculations [ Schmidt et al , ]. For CO 2 , the ab initio calculations [ Schmidt et al , ] reported 3 times stronger fractionations than predicted by the semiempirical approach applied by Liang et al []. Furthermore, Ndengué et al [] showed that the assumption by Liang et al [] of a proportional relationship between changes in absorption cross sections under isotopic substitution and changes in zero point energy for both central and terminal substitution is not valid.…”
Section: Discussionmentioning
confidence: 99%
“…For the bimolecular-collision reactions of Cl( 2 P 3/2 ) + X 2 (υ) → XCl + X(X = H, D) with para-H 2 and ortho-D 2 in the quantum solids, various isotope effects, which may be classified as energetic, translational amplitude, and kinematic, have been predicted based on the quantum reaction dynamics simulations [22]. In the photolysis of carbon dioxide (C 12,13 O 16,17,18 2 ), strong isotopic fractionation can occur as a function of wavelength [23]. In the non-dissociative photoionization spectrum of the N 14,15 2 molecule, significant changes in peak energies and intensities upon isotopic substitution were observed [24].…”
Section: Introductionmentioning
confidence: 99%
“…By convention, the delta notation, is used, which for oxygen is δ 18 For oxygen, the standard is standard mean ocean water (SMOW). Stable isotope ratio measurements are typically reported in this manner, and a similar isotope ratio is reported for δ 17 O. In general, isotope ratio alterations are attributable to conventional thermodynamic, kinetic, translational, and gravitational phenomena (4-6).…”
mentioning
confidence: 96%
“…The applications have subsequently expanded, particularly to oxygen isotopes, and in this special issue, many unique uses of both oxygen and sulfur isotopes are presented (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation